High Performance Computing in Science and Engineering ’03: Transactions of the High Performance Computing Center Stuttgart (HLRS) 2003 - Krause, Egon; Jäger, Willi; Resch, Michael (Springer Berlin Heidelberg, 2003)
This book presents the state of the art in modeling and simulation on supercomputers. Leading German research groups present their results achieved on high-end systems of the High Performance Computing Center Stuttgart (HLRS) for the year 2003. The reports cover all fields of computational science and engineering ranging from computational fluid dynamics via computational physics and chemistry to computer science. Special emphasis is given to industrially relevant applications. Presenting results for both vector-systems and micro-processor based systems, the book allows the reader to compare performance levels and usability of a variety of supercomputer architectures. In the light of the success of the Japanese Earth-Simulator, this book may serve as a guide book for a US response. The book covers the main methods in high performance computing. Its outstanding results in achieving highest performance for production codes are of particular interest for both the scientist and the engineer. The book comes with a wealth of color illustrations and tables of results
Keywords: Aufsatzsammlung; Supercomputer; Technik; Naturwissenschaften